Pengaruh Kompetensi Kerja, Pengelolaan Laboratorium Kesehatan, Monitoring dan Evaluasi terhadap Kinerja Pegawai Dimediasi oleh Kesesuaian Tugas Pokok di Lingkungan Balai Besar Laboratorium Biologi Kesehatan Kementerian Kesehatan - Wiguna, Khaery; Sinambela, Lijan Poltak (LPPM Institut Pendidikan Nusantara Global, 2025)
Employee performance is a crucial determinant of organizational success, particularly in laboratory management units that play a vital role in supporting service quality and operational effectiveness. This study aims to analyze the influence of competence, motivation, and laboratory management on employee performance, both directly and indirectly through mediating variables. A quantitative research approach was employed, utilizing a survey method involving laboratory staff from various institutions. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS 4 software. The research instruments were developed based on validated and reliable indicators. The findings demonstrate that both competence and motivation have a significant positive impact on employee performance. Meanwhile, laboratory management exerts a strong indirect influence on performance through its effect on enhancing motivation. Furthermore, motivation serves as a partial mediating variable between competence and employee performance. These results highlight that improving employee performance is not solely dependent on technical skills, but also on internal motivational factors and the presence of an effective laboratory management system. In conclusion, a human resource development strategy that integrates competence enhancement, motivational reinforcement, and optimal laboratory governance is essential for achieving superior employee performance. This integrated approach not only supports operational efficiency but also contributes to the sustainability and continuous improvement of service quality in laboratory-based organizations.